MUSIC THERAPY CLINICAL PRACTICE AND RESEARCH INITIATIVES IN INDIA: BRIDGE BETWEEN THE EXPERIENCES OF TRADITIONAL MUSIC HEALING PRACTICES AND ITS SCIENTIFIC VALIDATIONS (International Journal of Ayurveda and Pharma Research, 2018)
The aim of this review is to showcase and discuss about how music therapy clinical practice and research initiatives in India serve as a bridge between the experiences of traditional music healing practices and its scientific validations. The current status of these healing applications in the global framework of music therapy is highlighted. The multi-modal approach by which aspiring music therapists engage in clinical practice and research with an individualized approach to bring about the therapeutic outcome are presented. Traditional healing resources like Vedic chanting, Raga Cikitsa, Garbha Sanskara (Learning in the Womb), Time theory of ragas integrating the ancient Ayurvedic perspectives and Cakra activation (music and breathing technique using ragas) are enumerated. The clinical outcomes are reviewed as a way to impact biological, physiological, psychological, chrono-biological and spiritual dimensions.